Meningkatkan Keterampilan Sosial Melalui Model Pembelajaran Kooperatif Tipe Teams Games Tournament (Tgt) Siswa Sekolah Dasar - Candra, Denny; Ananda, Rizki; Sumianto, Sumianto (ANTHOR: Education and Learning Journal, 2022)
This study aims to improve sosial skills through the Teams Games Tournament (TGT) cooperatif learning model. This type of research is Classroom Action Research (CAR) which is carried out collaboratively with class teachers. This study consists of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were grade IV students of SDIT Insan Harapan Batam, consisting of 14 male students and 13 female students. The data collection method uses documentation, observasion and interview teachnique uses of the Teams Games Tournament (TGT) Cooperative learning model can improve the social skills of fourth grade studens of SDIT Insan Harapan Batam. This is indicated by an increase in the number of students who reach the Completion Criteria (MB) and an increase in Classics. The percentage value of classical completeness is 85%. Cycle I meeting 62.96% increased to 77.77% and 88.88% in cycle II meeting I and cycle II meeting II.Thus through the Cooperatif Teams Games tournament (TGT) learning model can improve thesocial skills of fourth grade students at SDIT Insan Harapan Batam.